Comprendre et respecter l’autre : le cas de l’autisme dans le roman pour adolescents et jeunes adultes - Kunešová, Květuše (Romanica Silesiana, 2021)
The article “Understand and Respect the Other: Autonomy and Autism in the Novel for Teenagers and Young Adults” is a comparative reflection of books that focus on the human relationships that are formed around young protagonists trying to find their own way and the true values of life. These are mostly realistic novels / mirror novels in which illness, disability or death represent a plot that puts the characters to the test. At crucial moments they are forced to deploy their energy and perseverance, and on that side, they learn to live and be independent. Novels about autism allow to consider new questions concerning identity and otherness, norm and outside the norm. The notion of freedom is viewed differently by the characters who are faced with the dilemma whether the need to care for the sick is a sacrifice or a duty.